Influences of magnetic field on wave propagation in generalized thermoelastic solid with diffusion - Abo-Dahab, S.M.; Singh, B. (Archives of Mechanics, 2009)
This paper is devoted to estimation of the influence of magnetic field in an elastic solid half-space under thermoelastic diffusion. The governing equations in xz-plane are solved taking into consideration the GL model. The reflection of dilatational (P) wave and shear vertical (SV) wave splits into four waves, namely: P wave, thermal wave, mass diffusion wave and SV wave. The reflection phenomena of P and SV waves from the free surface of an elastic solid with thermoelastic diffusion, under the influence of magnetic field is considered. The expressions for the reflection coefficients for the four reflected waves are obtained. These reflection coefficients are found to depend upon the angle of incidence θ of P and SV waves, thermoelastic diffusion, magnetic field and other material parameters. The numerical values for the reflection coefficients are calculated analytically and presented graphically for various values of these parameters. Relevant results of previous investigations are deduced as special cases from this study.